2021
DOI: 10.18332/ejm/142818
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant during the COVID-19 pandemic: Knowledge, concerns, attitudes and practices of Pakistani women

Abstract: INTRODUCTION Data regarding pregnancy and related outcomes with COVID-19 are inconsistent, which leads to difficulties in counselling pregnant women. This brings uncertainty to pregnant women regarding mode of birth, transmission and issues that may occur in case they contract the disease. We conducted this study to assess the knowledge about COVID-19 risk during pregnancy and childbirth and to assess the concerns, attitudes, and practices of pregnant women during the pandemic. METHODS A cross-sectional survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
1
11
1
Order By: Relevance
“…Our study demonstrates high awareness of COVID-19, its transmission mode, presenting symptoms and main preventive measures. The reported understanding is better than the studies conducted in Ethiopia and Pakistan 15 16. This can be attributed to the disease burden in the two study areas and the time of the survey.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Our study demonstrates high awareness of COVID-19, its transmission mode, presenting symptoms and main preventive measures. The reported understanding is better than the studies conducted in Ethiopia and Pakistan 15 16. This can be attributed to the disease burden in the two study areas and the time of the survey.…”
Section: Discussioncontrasting
confidence: 60%
“…The reported understanding is better than the studies conducted in Ethiopia and Pakistan. 15 16 This can be attributed to the disease burden in the two study areas and the time of the survey. Public awareness has been crucial in controlling the spread of COVID-19 as it is directly linked to the implementation of COVID-19-appropriate behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…The ndings of this study revealed that pregnant women experienced anxiety during the COVID-19 pandemic and a lack of knowledge regarding the impact of COVID-29 during the pregnancy process. Inadequate knowledge of pregnant women related to the risk of exposure to COVID-19 to mother and vertical transmission can increase negative attitudes toward preventing COVID-19 transmission 37,38 . Knowledge of pregnant women is mostly obtained from social media information, which has lower accuracy than information from health workers, newspapers, and the WHO or CDC website 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate knowledge of pregnant women related to the risk of exposure to COVID-19 to mother and vertical transmission can increase negative attitudes toward preventing COVID-19 transmission 37,38 . Knowledge of pregnant women is mostly obtained from social media information, which has lower accuracy than information from health workers, newspapers, and the WHO or CDC website 37 . Rumors, stigma, and conspiracies can affect the trust of pregnant women to misinformation and disinformation.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2, which causes COVID-19, exhibits human-to-human transmission by multiple means, namely by droplets, aerosols, and fomites [ 3 ]. Knowledge on COVID-19 in pregnant women has evolved tremendously; earlier reports from China considered the possibility of vertical transmission, but subsequent reports depicted a theoretical risk, and increased prevalence of preterm deliveries was also noticed [ 4 ].…”
Section: Introductionmentioning
confidence: 99%